IgG4-related disease presenting with hypercalcemia: case report and mechanistic insights - Li, Yaxin; Niu, Xing; Li, Ling; Hu, Zhangxue (Frontiers in Immunology, 2025)
Immunoglobulin G4-related disease (IgG4-RD) is a rare, multisystem disorder with diagnostic challenges. We report a case of IgG4-RD initially presenting with acute kidney injury (AKI) and hypercalcemia in a 61-year-old woman with a history of recurrent eyelid edema. On admission, serum creatinine and calcium were significantly elevated (414 μmol/L and 3.69 mmol/L, respectively). After excluding other etiologies, diagnosis was confirmed by renal biopsy and elevated serum IgG4 levels. Treatment with prednisone acetate and supportive care resulted in gradual clinical and laboratory improvement. This case underscores the importance of considering IgG4-RD in patients with unexplained AKI and hypercalcemia, highlighting the value of early diagnosis and targeted therapy. Furthermore, we explored potential pathophysiological mechanisms underlying hypercalcemia in IgG4-RD and found that M2 macrophages may overexpress 1α-hydroxylase, enhancing the conversion to active 1,25(OH)2D, and thereby increasing intestinal calcium absorption and leading to hypercalcemia, which has also been described in granulomatous diseases.